2016
DOI: 10.1007/978-3-319-27511-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in Healthy Skeletal Muscle and Metabolic Disease

Abstract: Adipose tissue not only functions as a reserve to store energy but has become of major interest as an endocrine organ, releasing signalling molecules termed adipokines which impact on other tissues, such as skeletal muscle. Adipocytes, within skeletal muscle and adipose tissue, secrete adipokines to finely maintain the balance between feed intake and energy expenditure. This book chapter focuses on the three adipokines, adiponectin, leptin and IL-6, which have potent effects on skeletal muscle during rest and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 169 publications
1
28
0
1
Order By: Relevance
“…In this study, mice exposed to 10 weeks of an HF diet recapitulated the key problems of MetS [28]: an increased caloric intake, reflecting reduced satiety control, as well as increased body weight and fat mass associated with impaired glucose tolerance. Paradoxically, these disturbances were associated to an increased plasmatic leptin level, a hormone reducing food intake and increasing energy expenditure, insulin sensitivity and fat deposition [29]. These results could be explained by a leptin resistance, preventing its central and peripheral functions [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice exposed to 10 weeks of an HF diet recapitulated the key problems of MetS [28]: an increased caloric intake, reflecting reduced satiety control, as well as increased body weight and fat mass associated with impaired glucose tolerance. Paradoxically, these disturbances were associated to an increased plasmatic leptin level, a hormone reducing food intake and increasing energy expenditure, insulin sensitivity and fat deposition [29]. These results could be explained by a leptin resistance, preventing its central and peripheral functions [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AMPK activation by phosphorylation can reduce the degree of obesity by inhibiting adipocyte differentiation by changing the expression and activity of the enzymes and proteins involved in lipid metabolism (16,19). Furthermore, ACC, a downstream substrate of AMPK, is a rate-limiting enzyme that limits the critical rates in fatty acid synthesis and oxidation, reducing the fatty acid and lipid synthesis to inhibit the onset and progression of obesity (13,18). Therefore, AMPK signaling has gained the attention of researchers as a molecular target for fighting obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMKP inhibits preadipocyte differentiation and adipogenesis through increased phosphorylation of ACC, a substrate of AMPK (13,17). To investigate whether AMPK is activated by EEAY during 3T3-L1 differentiation, we analyzed the levels of phosphorylated AMPK and ACC and found that EEAY remarkably enhanced the phosphorylation of AMPK and ACC without altering the expression of their total protein expression, indicating the activation of the AMPK pathway.…”
Section: Eeay Induces the Phosphorylation Of Ampk And Accmentioning
confidence: 99%
See 2 more Smart Citations